After: A Doctor Explores What Near-Death Experiences Reveal about Life and Beyond by Bruce Greyson - Alexander, John B. (Journal of Scientific Exploration, 2022)
After portrays the epic journey of a true skeptic who chose to follow the data rather than reject seemingly fantastical accounts from his patients. It is an account of transformation while maintaining a thoughtful balance accommodating both spiritual and material worldviews. Spurred on by serendipitous events, uniquely Greyson has spent more than four decades chasing the previously inexplicable, and gossamer-like, but tantalizing glimpses of what was reported to be the continuation of consciousness beyond physical existence. There have been a number of compelling books describing detailed accounts of those who pierced the veil and returned to report on it. In Proof of Heaven, Dr. Eben Alexander, a neurosurgeon with more than two decades of experience, first related his extensive interactions in the nether realms while suffering from gram-negative meningitis; a condition from which he was not expected to survive. Dr. Mary Neal incredibly was revived after more than 30 minutes submerged in the raging waters in the Los Rios region in southern Chile. Writing To Heaven and Back, similarly, she reported events that can only be described as miracles and extracorporeal encounters with heavenly deities. While discarnate, she was provided accurate information of events that tragically would come to pass, thus substantiating the validity of that experience. Those books, and many others, provide insightful details into often dramatic experiences. What Greyson brings to the table is more than four decades of intensive research and examination of thousands of reported near-death experiences (NDE’s), the breadth and depth of which are unparalleled.